Health Information Systems Technological and Management Perspectives - Winter, Alfred; Ammenwerth, Elske; Haux, Reinhold; Marschollek, Michael; Steiner, Bianca; Jahn, Franziska; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This heavily revised open access edition provides a thorough overview of the technologies available to assemble, manage and assess the quality of health information systems. It details a variety of scenarios in the context of both health and heath care, including where prevention and wellness are related, such as the treatment of both acute and chronic diseases. Stakeholder requirements are also described to provide perspectives for describing the architectures and management techniques associated with health information systems, enabling the reader to develop a detailed holistic overview of the subject. Health Information Systems: Technological and Management Perspectives features a detailed overview of how information systems in health care can be managed and is a vital resource for medical informatics students seeking an up-to-date text on the topic.
Introduction -- Motivation And Objective Of The Book -- Life Situations -- Stakeholders$1 (BRequirements -- Example -- Summary -- Basic Concepts And Terms -- Introduction -- Data, Information And Knowledge -- Systems And Subsystems -- Information Systems -- Health Information Systems -- Information Logistics In Health Information Systems -- Functions And Processes Of Health Care Settings -- Information Processing Tools Of Health Information Systems -- Electronic Health Records As A Part Of Health Information Systems -- Architecture And Infrastructure Of Health Information Systems -- Management Of Health Information Systems -- Modeling Information Systems -- Using The Snik Ontology Together With This Book -- Examples -- Exercises -- Summary -- Technological Perspective: Architectures, Integration And Standards -- Introduction -- Layers Of Architectures -- Integrity And Integration -- Standards For Interoperability -- Specific Health Information Systems -- Examples -- Exercises -- Summary -- Management Perspective: Tasks,Scope And Governance -- Introduction -- Strategic, Tactical And Operational Management Of Information Systems -- Tasks And Methods Of Strategic Management Of Information Systems -- It Service Management -- Data Governance -- It Governance -- Managing Specific Health Information Systems -- Examples -- Exercises -- Summary -- Quintessence: Quality -- Fulfillment Of Stakeholders$1 (BRequirements -- Evaluation -- Summary -- Thesaurus -- Literature Cited. .s
Keywords: Medical informatics; Health Informatics